UNIVERSITY AUTONOMY - A SUFFICIENT OR NECESSARY CONDITION FOR THE QUALITY OF HIGHER EDUCATION? EXPERIENCE OF EDUCATIONAL DEBATES - Oksana Bulvinska (Borys Grinchenko Kyiv Metropolitan University, 2024)
The article is dedicated to presenting the experience of conducting debates on the impact of university autonomy on the improvement of higher education quality. It emphasizes that university autonomy is a fundamental academic value and a strategic direction of development for the European Higher Education Area, as well as a key feature of a democratic society and a condition for enhancing the quality of higher education and research. Debates are characterized as an educational technology and their role in the development of professional and general competencies of third-level (educational-scientific level) higher education seekers, enhancing the level of communication skills and interactive ability for partnership interaction, teamwork skills, as well as affirming democratic values, tolerance, honesty, and respect for opponents. The arguments presented by members of the affirmation team during the debates demonstrated that university autonomy in all four dimensions (organizational, personnel, financial, and academic) allows for the creation of a self-regulated and authoritative environment conducive to improving the quality of higher education, and also obliges universities to bear responsibility to society, as they play a key role in the development of a democratic and inclusive society, sustainable and environmentally safe economic and social development, in the development of the economy and improvement of living standards. In contrast, the opposing team argued the possibilities of centralized regulation by the state in enhancing the quality of higher education and in the implementation of universities' social responsibility.